Treatment of Crimean-Congo hemorrhagic fever - (:unkn) unknown (ELSEVIER, 2008)
Crimean-Congo hemorrhagic fever (CCHF) has the most extensive geographic range of the medically significant tick-borne viruses, occurring from western China across southern Asia to eastern Europe and South Africa. The causative agent is a negative-sense, single-stranded RNA virus in the genus Nairovirus, family Bunyaviridae. In published reports, the case fatality rate has generally ranged from 10% to 50%. Sporadic cases and outbreaks of the disease have increased during the past decade across the endemic region. CCHF was first diagnosed in Turkey in 2002, but since then more than 1100 cases have been confirmed by IgM serology or RT-PCR, with a fatality rate of just over 5%. Simple methods are available for the in vitro evaluation of antiviral drugs, but because CCHF virus does not cause disease in its reservoir species or in laboratory animals other than suckling mice, methods are lacking for in vivo efficacy testing. Intravenous or oral ribavirin has been used in several countries to treat the disease for more than 20 years. Evidence of its efficacy is limited to observational studies, and placebo-controlled trials may be impossible to perform for ethical reasons. However, careful analysis of properly stratified observational studies can be used to assess the effects of treatment. This article reviews current approaches to the treatment of CCHF, focusing on the use of ribavirin and hematological support, and discusses prospects for future research. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Crimean-Congo hemorrhagic fever; ribavirin; bunyavirus; emerging infections; viral hemorrhagic fever; arbovirus; antiviral therapy; biodefense; ANTIVIRAL ACTIVITY; EXONUCLEASE ISG20; ORAL RIBAVIRIN; RISK-FACTORS; VIRUS; INHIBITION; EFFICACY; PROTEIN; REPLICATION; THERAPY